Effect of L-leucine supplementation on growth performance and carcass characteristics of grower-broiler chickens fed low protein diets - Edi Erwan,; Alimon, Abdul Razak; Sazili, Awis Qurni; Yaakub, Halimatun; Abdullah, Muhammad Hilmi (Science Publications, 2009)
Problem statement: Supplementation of broiler diets with cristalline amino acids (i.e. lysine, ethionine and threonine) may support equal broiler growth and improve overall amino acids balance and enable a reduction in CP level of diets. Approach: A trial was conducted to evaluate the effect of supplemental L-leucine in diets containing recommended levels and low crude protein (20 and 18%, respectively) with constant metabolizable energy (3200 kcal kg-1) for broilers from 21- 42 day of age. Six experimental diets were formulated with three levels of supplemental L-leucine, 0, 0.5 and 0.67% and two levels of crude protein. A total of 180 1 day-old Cobb broiler chickens were randomly divided into 36 experimental pens, 5 chickens in each pen, with each diet replicated 6 times. The dietary treatments were offered from 21-42 days of age. Feed intake, body weight gain and Feed Conversion Ratio (FCR) were measured on a weekly basis. At the end of the feeding trial the birds were slaughtered and carcass analyses conducted. Results: Feed intake, weight gain and FCR were not affected by increasing levels of L-leucine supplementation. Weight gain was significantly reduced (p<0.05), whereas feed intake and FCR were not significantly affected with decreasing dietary crude protein. A positive response in breast meat yield was achieved by the addition of L-leucine to levels up to 0.5% in the diet but a significant decrease was noted when the level reached 0.67% in diet. Supplementation of L-leucine significantly (p<0.05) decreased the relative weights of the liver and gizzard. However, the addition of L-leucine significantly reduced carcass weights when L-leucine was added at 0.67%. Lowering the dietary protein level also significantly reduced breast yield and carcass weight (p<0.05). However, abdominal fat, gizzard, liver and heart were not affected by protein level. Conclusion/Recommendations: It can be concluded that supplementation of L-leucine at levels up to 0.67% of the diet did not affect performance but deleteratious the carcass weight.